2020
DOI: 10.1177/0033294120954135
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Occupational Burnout Among Ophthalmologists: A Systematic Review and Meta-Analysis

Abstract: Objective To investigate the prevalence of occupational burnout among ophthalmologists in order to better understand the mental and physical well-being of eye physicians and surgeons in the professional workplace. Study Design A systematic review and meta-analysis. Methods Online computer databases MEDLINE, EMBASE, CINAHL, and ProQuest Dissertations and Theses were searched systematically and thoroughly. Conferences held through Association for Research in Vision and Ophthalmology, American Academy of Ophthalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
(78 reference statements)
0
5
0
1
Order By: Relevance
“…13 In a prospective cohort study where physicians were surveyed in medical school and then again during year 2 of residency, ophthalmology residents were at a higher relative risk for reporting burnout symptoms compared with other clinical specialties with a burnout prevalence of 55.8%. 17,22 In a survey of the U.States. ophthalmic residents, only 26.7% of respondents reported a formal resident wellness program despite the fact 68.4% reported depression, burnout, or suicide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In a prospective cohort study where physicians were surveyed in medical school and then again during year 2 of residency, ophthalmology residents were at a higher relative risk for reporting burnout symptoms compared with other clinical specialties with a burnout prevalence of 55.8%. 17,22 In a survey of the U.States. ophthalmic residents, only 26.7% of respondents reported a formal resident wellness program despite the fact 68.4% reported depression, burnout, or suicide.…”
Section: Discussionmentioning
confidence: 99%
“…14 Previously, a meta-analysis of 9 total studies reported significant rates of burnout in ophthalmology (effective size = 0.41; CI [0.26-0.56]), with a high prevalence of emotional exhaustion, depersonalization, and low sense of personal accomplishment among 1408 subjects. 17 Of the 9 included studies, 5 were from the United States, including 3 regarding resident physicians only and 1 regarding academic chairs only. Although this meta-analysis is in overall agreement with the results of our investigation, comparison of methods and demographics are limited because of study heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…A heavy workload prevents the physician from taking even short breaks, which could increase PA levels, even unintendedly. This finding is a potential contributor to the established damage to physician wellness caused by excessive workload (Wallace et al, 2009) and to the burnout of ophthalmologists in particular (Cheung et al, 2020). In an era of health care systems that maximize profitability, the long-term well-being of health care providers needs to be prioritized.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it may be that there is overuse of trainee labour to enable greater work/life balance amongst ophthalmologists at STP posts. With excessive workloads linked to burnout, 15 efforts to cap workloads for trainees may therefore be needed, especially to allow for engagement with the community which is essential for facilitating rural connection and subsequent rural recruitment 9 . Ironically, efforts to cap trainee workloads may inadvertently increase the likelihood of practising ophthalmologists leaving STP posts given that in hours workload and after‐hours workload are key factors impacting retention 9,16 .…”
Section: Discussionmentioning
confidence: 99%